Assessing the Robustness of Quantitative Fatty Acid Signature Analysis to Assumption Violations (Supplementary Data) - Bromaghin, J. F.,; Budge, S. M.,; Thiemann, G. W.,; Rode, K. D. (USGS Science Data Catalog, 2015)
This dataset contains fatty acid (FA) data expressed as mass percent of total FA for bearded seals, ringed seals and walrus. This is one of many datasets used in Bromaghin et al., In press, Assessing the robustness of quantitative fatty acid signature analysis to assumption violations, Methods in Ecology and Evolution. These supplemental data were used in computer simulations to compare the bias of several quantitative fatty acid signature analysis (QFASA) estimators and develop recommendations regarding estimator selection.